2018
DOI: 10.4491/eer.2018.082
|View full text |Cite
|
Sign up to set email alerts
|

Anaerobic codigestion of urban solid waste fresh leachate and domestic wastewaters: Biogas production potential and kinetic

Abstract: The Biochemical Methane Potential (BMP) of fresh leachate and domestic wastewaters codigestion was determined by laboratory Bach Tests at 35ºC over a period of 90 d using a wide range of leachates volumetric ratios from 0% to 100%. To simulate wastewaters plant treatment step, all the ratios were first air stripped for 48 h before anaerobic incubation. The kinetic of biogas production was assessed using modified Gompertz model and exponential equation. The results obtained showed that cumulative biogas product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 39 publications
1
0
0
Order By: Relevance
“…Up today, few works have been consecrated to fresh (before dumping) waste leachates recovery and no work was done regarding anaerobic recovery of Moroccan municipal solid wastes leachates. In previous work, we confirmed that codigestion of similar fresh leachates with wastewater is feasible and could be a potential alternative for an eventual centralized treatment at biogas recovery-based wastewater plants in Morocco [45].…”
Section: Introductionsupporting
confidence: 76%
“…Up today, few works have been consecrated to fresh (before dumping) waste leachates recovery and no work was done regarding anaerobic recovery of Moroccan municipal solid wastes leachates. In previous work, we confirmed that codigestion of similar fresh leachates with wastewater is feasible and could be a potential alternative for an eventual centralized treatment at biogas recovery-based wastewater plants in Morocco [45].…”
Section: Introductionsupporting
confidence: 76%